2017
DOI: 10.5897/ijppb2017.0266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pisum sativum L. cytokinin and auxin metabolic and signaling genes, and an analysis of their role in symbiotic nodule development

Abstract: The present work was designed to study the role of the phytohormones, cytokinin and auxin, in the symbiosis development between pea Pisum sativum L. and Rhizobium leguminosarum bv. viciae. To achieve this aim, the temporal expression patterns of the genes related to the cytokinin and auxin biosynthesis, perception, and response were studied. It was found that most of these genes showed specific transcriptional regulations upon nodulation at various stages following inoculation. Once they were purified using ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Increased levels of trans-zeatin riboside were found in the mycorrhizal roots when compared with non-mycorrhizal roots in some legume plants [ 60 ]. The activation of type-A and type-B cytokinin response regulators (type-A RR and type-B RR ) was shown to be related to cytokinin receptor activation in legume plants [ 61 , 62 , 63 ]. Indeed, our experiments showed that the expression of type-A cytokinin response genes RR4 , RR6 , RR8 , and RR9 increased in wild-type roots within 14 days of infection with AM fungi ( Figure 9 A).…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of trans-zeatin riboside were found in the mycorrhizal roots when compared with non-mycorrhizal roots in some legume plants [ 60 ]. The activation of type-A and type-B cytokinin response regulators (type-A RR and type-B RR ) was shown to be related to cytokinin receptor activation in legume plants [ 61 , 62 , 63 ]. Indeed, our experiments showed that the expression of type-A cytokinin response genes RR4 , RR6 , RR8 , and RR9 increased in wild-type roots within 14 days of infection with AM fungi ( Figure 9 A).…”
Section: Resultsmentioning
confidence: 99%
“…In pea, a two-stage increase in the content of CKs during nodule development was observed ( Dolgikh et al, 2017 ). The accumulation of tZ and IP at 3 dpi can be associated with cortical cell division where CKs are known to be positive regulators, while the increase of tZ content at later stages suggests that CK also plays a role in subsequent stages of the nodule development and functioning ( Dolgikh et al, 2017 ). The temporal expression dynamics of MtIPT s we observed are in line with this observation, suggesting that cytokinin biosynthesis also occurs at later stages of nodule development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RNA-seq analysis shows the expression of some LOG genes along with that of CYP735A1 gene (Medtr6g017325) in the epidermis of inoculated roots ( Jardinaud et al, 2016 ). Activation of IPT and LOG genes has also been demonstrated in nodules of Pisum sativum ( Azarakhsh et al, 2015 ; Dolgikh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 95%
“…It was shown that expression of some PsLOG and PsIPT genes may depend on the Ps KNOX3 transcription factor in pea (Azarakhsh et al, 2015). To investigate a possible link between regulation of transcription factors by DELLA and possible targets of KNOX transcription factors, we have examined the PsLOG1, PsLOG2, PsIPT1, PsIPT2, PsIPT3 , and PsIPT4 (all of them encode enzymes that belong to adenosine phosphate-IPTs) expression in LA cry and la cry mutants during nodulation (2, 9, and 14 dai) (Figure 3, 4), because their up-regulation was shown upon nodulation in pea (Azarakhsh et al, 2015; Dolgikh et al, 2017). However, as the level of IPT3 was very low in cv.…”
Section: Resultsmentioning
confidence: 99%
“…Plant material was ground with a mortar and pestle to a fine powder in liquid nitrogen. Approximately 50–100 mg of ground tissue was used for RNA extraction, as previously described (Dolgikh et al, 2017). 1–2.5 μg of total RNA was used to synthesize cDNA with the RevertAid Reverse Transcriptase (Thermo Fisher Scientific, United States).…”
Section: Methodsmentioning
confidence: 99%